2014
DOI: 10.1007/s00268-014-2684-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of Pancreatic Juice Cytology in the Preoperative Management of Intraductal Papillary Mucinous Neoplasm of the Pancreas in the Era of International Consensus Guidelines 2012

Abstract: Pancreatic juice cytology potentially has important roles to determine the adequate treatment choice in patients with IPMNs with "worrisome features," and to detect significant lesions that could not be detected by other imaging modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
(60 reference statements)
0
21
1
Order By: Relevance
“…At present, only invasive carcinoma derived from IPMN is considered malignant, and high-grade dysplasia is not considered malignant [4,6]. However, this has recently been questioned, as there have been some reported cases of high-grade dysplasia recurring as a distant metastasis after resection [8,9]. High-grade dysplasia is regarded as an indication for surgical resection as stated in the Fukuoka guidelines [4], although it is not clearly defined as malignant [6].…”
Section: Definitions and Classificationmentioning
confidence: 99%
“…At present, only invasive carcinoma derived from IPMN is considered malignant, and high-grade dysplasia is not considered malignant [4,6]. However, this has recently been questioned, as there have been some reported cases of high-grade dysplasia recurring as a distant metastasis after resection [8,9]. High-grade dysplasia is regarded as an indication for surgical resection as stated in the Fukuoka guidelines [4], although it is not clearly defined as malignant [6].…”
Section: Definitions and Classificationmentioning
confidence: 99%
“…In addition to a mural nodule and dilated MPD, several studies have found that cytology and/or tumor markers, including carcinoembryonic antigen (CEA) in the cystic fluid obtained by EUS-guided fine needle aspiration (EUS-FNA), or in the pancreatic juice obtained from MPD by endoscopic retrograde pancreatography (ERP), were useful to establish surgical indication for IPMN [36][37][38][39][40][41]. The diagnostic accuracy of cystic fluid or pancreatic juice cytology for HGD/invasive IPMC is poor because the sensitivity rate is low [36][37][38]. However, the positive predictive value (PPV) of cytology for HGD/invasive IPMC is excellent and might be a useful method to determine surgical indication [36,37].…”
Section: Predictive Factors Associated With Hgd/invasive Ipmcmentioning
confidence: 99%
“…73 In contrast, an evaluation of pancreatic juice cytology obtained by routine preoperative ERCP in 70 patients with IPMN found that the addition of pancreatic juice cytology altered treatment in two patients with branch-duct (BD)-IPMN from observation to surgical resection. 74 Moreover, three IPMNconcomitant pancreatic ductal adenocarcinomas (PDAC) were diagnosed only by ERCP that included pancreatic juice cytology. One potential drawback of ERCP assessment of pancreatic juice cytology, however, is post-ERCP pancreatitis (PEP).…”
Section: Assessment Of Pancreatic Juice By a Transpapillary Approachmentioning
confidence: 99%